PERAN GURU KRISTEN DALAM PEMBELAJARAN MATEMATIKA DI SUATU SEKOLAH KRISTEN DI TANGERANG [CHRISTIAN TEACHER’S ROLE IN LEARNING MATHEMATICS AT A CHRISTIAN SCHOOL IN TANGERANG] - Imran, Septianus; Hidayat, Dylmoon; Winardi, Yonathan (Universitas Pelita Harapan, 2019)
This research used a qualitative approach with a case study design in a Christian school in Tangerang. The research’s subjects included eight mathematics teachers and 143 students from different classes, each one taught by the eight mathematics teachers. Data collection was based on interviews, observations, and distributing questionnaires. The data analysis used the Miles and Huberman model which consists of three processes: data reduction, data display, and conclusion drawing. The research results showed that student negative behaviours included having a low self value in mathematics, saying negative words to classmates, being disrespectful towards the mathematics teachers, abusing the learning environment, and assuming God has no connection with mathematics learning. To redeem student negative behaviours, mathematics teachers at the school gave advice, warnings, consequences, and attempted to be a role model for students. Student responses towards teachers' actions can be grouped into two categories: positive responses: students receive advice, warnings, concequences and repair their negative behaviour and negative responses: students think trivially about advice, warnings, or consequences given by teachers.BAHASA INDONESIA ABSTRACT: Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus di suatu sekolah Kristen di Tangerang. Subjek penelitiannya adalah delapan guru Matematika dan 143 orang siswa-siswi yang masing-masing diajar oleh delapan guru tersebut. Pengumpulan data menggunakan teknik wawancara, observasi, dan penyebaran kuesioner. Teknik analisis data menggunakan model Miles dan Huberman yang terdiri dari tiga tahap yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bentuk-bentuk perilaku negatif siswa, yaitu menilai diri rendah dalam Matematika, mengeluarkan kata-kata negatif kepada teman kelas, tidak menghargai atau menghormati guru Matematika, menyalahgunakan lingkungan belajar, serta menganggap Tuhan tidak ada kaitannya dengan Matematika. Untuk memulihkan perilaku negatif siswa, guru Matematika di sekolah Kristen tersebut memberi nasihat, teguran, konsekuensi, serta berusaha menjadi teladan akan kesabaran, ketegasan dan pengampunan bagi siswa-siswinya. Respon siswa terhadap tindakan guru dikelompokkan menjadi dua kategori, yaitu positif: siswa menerima nasihat, teguran, maupun konsekuensi dan merubah perilaku negatifnya dan respon negatif: siswa menganggap sepele nasihat, teguran atau konsekuensi yang diberikan guru.